The Use of Matching Game to Improve Students’ Vocabulary - Muhammad Djawhary Al-Audh; Maemuna Muhayyantg; Geminastiti Sakkir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The aim of this study was to know the impact of the Matching Game on students’ vocabulary mastery. This research method was a pre-experimental design. The population of this research was the seventh-grade students of SMPN 1 Bajeng in academic year 2022/2023 through a convenience sampling technique. The sample of the research is seventh grade D which consists of 31 students. The pre- and post-tests for the research's vocabulary test were given. The results of the study demonstrated that vocabulary development in students can benefit from the use of matching games. It was established that the pre-test mean score for students was 50.19, while the post-test mean score for students was 68.13. The usage of a matching game could enhance students' vocabulary, according to the statistics.Keywords— Matching Game, Vocabulary Mastery.